2007
DOI: 10.1111/j.1095-8649.2007.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of European spined loaches (genus Cobitis L.): an update of the geographic distribution of the Cobitis taenia hybrid complex with a description of new molecular tools for species and hybrid determination

Abstract: Although the unique features of asexual reproduction and hybridization among European spined loaches (genus Cobitis) have recently attracted the attention of conservation biologists, faunists and evolutionary biologists, the research has suffered from uncertain identification of specimens and their genomes because of the extreme morphological similarity of all the species within the hybrid complex. In this article, a Europe-wide study is reported, which was performed on samples collected by several research te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
147
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(157 citation statements)
references
References 23 publications
6
147
3
1
Order By: Relevance
“…It means that the genome of these triploid fish raised as a consequence of hybridization process among three following species: Cobitis elongatoides, C. taenia and C. taurica. The same genome constitution of triploid hybrids from the Bug River (Poland) has been previously reported also by Janko et al (2007), and then it has been confirmed in investigations conducted by Maciak et al (2011).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…It means that the genome of these triploid fish raised as a consequence of hybridization process among three following species: Cobitis elongatoides, C. taenia and C. taurica. The same genome constitution of triploid hybrids from the Bug River (Poland) has been previously reported also by Janko et al (2007), and then it has been confirmed in investigations conducted by Maciak et al (2011).…”
Section: Resultssupporting
confidence: 66%
“…Most of the studies published so far contain data on the chromosome number and karyotype of Cobitis taxa. In a few recent papers there are data on the chromosome structure of some Cobitis species obtained by classical chromosome banding and/or by molecular methods (Boroń 1999;Boroń & Kotusz 1999Ráb et al 2000;Rábová et al 2001Rábová et al , 2004Saitoh 2003;Janko et al 2005Janko et al , 2007Boroń et al 2006). However, little cytogenetic information is available for polyploid Cobitis taxa (Boroń & Danilkiewicz 1999;Rábová et al 2004;Boroń et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It concerned 11 orders, 17 families and 72 species. The selection of collection localities covered the main distribution areas of the studied taxa according to comprehensive surveys and the most recent taxonomic and phylogenetic studies (Baruš & Oliva, 1995;Hanel & Lusk, 2005;Kottelat & Freyhof, 2007;Janko et al, 2007;Mendel et al, 2008d, etc). The collection of samples was divided into three levels: -classification of the first level is based on the hydrologic position of the Czech Republic ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…C. elongatoides and C. tanaitica hybridize downstream (Mezhzherin, Pavlenko, 2007) and in middle reaches (Janko et al, 2007). In the case of hybrids of C. elongatoides × C. tanaitica backcrossing, triploid biotypes C. 2 elongatoides -tanaitica and C. elongatoides -2 tanaitica occur, while triploid biotypes C. elongatoides -tanaitica -taenia and C. elongatoides -tanaitica -2 taenia form upstream in the basin at the point of contact of C. elongatoides and С. taenia (Janko et al, 2007). Th erefore, it is quite correct to consider the Danube to be the place of origin of most European triploid biotypes of spined loaches, from where they have begun to invade other European river systems.…”
mentioning
confidence: 99%